Histopathology of the tongue in a hamster model of COVID-19 - John Coggins; Marina Hosotani Saito; Rebecca Cook; Shinji Urata; Megumi Urata; Nantian Lin Harsell; Wilhelmina Nanrui Tan; Bibiana Toro Figueira; Megan Bradley; Nadia Z. Quadri; Janisah Amirah I. Saripada; Rachel A. Reyna; et al. (BMC Oral Health)
Abstract Objective With altered sense of taste being a common symptom of coronavirus disease 2019 (COVID-19), the main objective was to investigate the presence and distribution of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) within the tongue over the course of infection. Methods Golden Syrian hamsters were inoculated intranasally with SARS-CoV-2 and tongues were collected at 2, 3, 5, 8, 17, 21, 35, and 42 days post-infection (dpi) for analysis. In order to test for gross changes in the tongue, the papillae of the tongue were counted. Paraffin-embedded thin sections of the tongues were labeled for the presence of SARS-CoV-2 antigen. Results There was no difference in fungiform or filiform papillae density throughout the course of infection. SARS-CoV-2 antigen was observed in the vallate papillae taste buds (3–35 dpi) and autonomic ganglia (5–35 dpi), as well as in the serous and mucous salivary glands of the posterior tongue (2–42 dpi). Conclusion The presence and distribution of SARS-CoV-2 suggest that the virus could cause taste disturbance by infecting the vallate papillae taste buds. This effect could be exacerbated by a diminished secretion of saliva caused by infection of the serous salivary glands and the autonomic ganglia which innervate them.